Elements of mother's psychopathology as risk factors for the development of negative self-concept and depressive symptomatology in the child - Μακρή-Μπότσαρη, Εύη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF